CRISPR-Cas13-Mediated Knockdown of Regulator of G-Protein Signaling 8 (RGS8) Does Not Affect Purkinje Cell Dendritic Development - Wu, Qin-Wei; Kapfhammer, Josef P. (Frontiers in Cell and Developmental Biology, 2022)
CRISPR-Cas13 technology is rapidly evolving as it is a very specific tool for RNA editing and interference. Since there are no significant off-target effects via the Cas13-mediated method, it is a promising tool for studying gene function in differentiating neurons. In this study, we designed two crRNA targeting regulator of G-protein signaling 8 (RGS8), which is a signaling molecule associated with spinocerebellar ataxias. Using CRISPR-Cas13 technology, we found that both of crRNAs could specifically achieve RGS8 knockdown. By observing and comparing the dendritic growth of Purkinje cells, we found that CRISPR-Cas13-mediated RGS8 knockdown did not significantly affect Purkinje cell dendritic development. We further tested the role of RGS8 by classical RNAi. Again, the results of the RNAi-mediated RGS8 knockdown showed that reduced RGS8 expression did not significantly affect the dendritic growth of Purkinje cells. This is the first example of CRISPR-Cas13-mediated gene function study in Purkinje cells and establishes CRISPR-Cas13-mediated knockdown as a reliable method for studying gene function in primary neurons.